Ecotourism in Colombian Peacebuilding: Peace, Conflict and Environmental Justice - Luis Fernando Sánchez Supelano (Via@)
With the aim of demonstrating the tensions faced in the implementation of ecotourism projects in Colombia, this paper discusses the role of armed conflict in the generation of environmental conflict in Colombia, and the way in which this has been increasing in recent years due to the arrival of new actors across different territories. Next, some of the contents of the peace agreement which impact ecotourism are reviewed in order to form a conclusion based on the need to adopt an approach based on environmental justice in the implementation of ecotourism, as a means of creating appropriate respect for environmental limits and the rights of the communities involved.